Female Sex and Obesity Are Risk Factors for Inadequate Calcium Intake in Youth With Type 1 Diabetes - Rahmani, Roman; Stevens, Elizabeth; Rackovsky, Noya; O’Brien, Kimberly O.; Schwartz, George J.; Weber, David R. (Frontiers in Clinical Diabetes and Healthcare, 2021)
People with type 1 diabetes (T1D) are at increased risk of developing low bone mineral density and fractures. Optimization of calcium intake is a key component of pediatric bone health care. Despite the known risk factors for impaired bone health in T1D and the known benefits of calcium on bone accrual, there are limited data describing calcium intake in youth with T1D. In this cross-sectional study, calcium intake was assessed in 238 youth with T1D. One third of study participants were found to have inadequate calcium intake. Female sex, especially during adolescence, and obesity were identified as specific risk factors for inadequate calcium intake. Given the known adverse effects of T1D on bone health, efforts to promote calcium intake in youth with T1D should be considered.